Pembelajaran Pendidikan Agama Hindu Di Sekolah Menengah Kejuruan Negeri 2 Sukawati Gianyar - Oka Wartini, Ni Luh Made; Temon Astawa, I Nyoman; Sudarsana, I Ketut (Metta : Jurnal Ilmu Multidisiplin, 2021)
Learning Hinduism at SMK Negeri 2 Sukawati in fact still tends to be teacher-centered, resulting in passive learners in the learning process. In addition, the cultivation of noble values ​​in accordance with the objectives of national education and Hindu religious education has not been 100% achieved. Based on this, there is a gap from the main learning objectives of Hindu religious education in shaping the character of students who have noble character and good ethical values ​​that have not been reflected in some students as expected by the community and their school environment. Therefore, choosing the right learning model is necessary so that the objectives of learning can be achieved. The theories used in analyzing the above problems are: Behavioristic learning theory and communication theory. This type of research is qualitative research. This research is located at SMK Negeri 2 Sukawati. The technique of determining informants in this study was using purposive technique. whereas in data collection using the method of observation, interviews, documentation, literature study systematically using data analysis techniques and presented with the technique of presenting the results of data analysis. The results showed the Hindu religious learning model at SMK Negeri 2 Sukawati used a contextual learning model, a problem-based learning model, and a direct learning model.